Gastric bypass simultaneously improves adipose tissue function and insulin-dependent type 2 diabetes mellitus - Billeter, Adrian; Vittas, Spiros; Israel, Barbara; Scheurlen, Katharina; Hidmark, Asa S.; Fleming, Thomas; Kopf, Stefan; Büchler, Markus W.; Müller, Beat P. (Langenbeck's archives of surgery, 2017)
ObjectiveThe underlying causes of type 2 diabetes (T2DM) remain poorly understood. Adipose tissue dysfunction with high leptin, inflammation, and increased oxidative stress may play a pivotal role in T2DM development in obese patients. Little is known about the changes in the adipose tissue after Roux-Y gastric bypass (RYGB) in non-severely obese patients (BMI < 35 kg/m2) and since these patients have more T2DM-associated complications than obese patients (“obesity paradox”), we investigated changes in adipose tissue function in a cohort of BMI <35 kg/m2 with insulin-dependent T2DM after RYGB surgery which resolves T2DM.MethodsTwenty patients with insulin-dependent T2DM and BMI <35 kg/m2 underwent RYGB. Insulin-resistance, leptin, oxidative stress, and cytokines were determined over 24 months. Expression of cytokines and NF-kappaB pathway genes were measured in leukocytes (PBMC). Adipose tissue inflammation was examined histologically preoperatively and 24 months after RGYB in subcutaneous adipose tissue.ResultsInsulin-resistance, leptin, oxidative stress as well as adipose tissue inflammation decreased significantly after RYGB. Similarly, systemic inflammation was reduced and peripheral blood mononuclear cells (PBMCs) were reprogrammed towards an M2-type inflammation. Loss of BMI correlated with leptin levels (r = 0.891, p < 0.0001), insulin resistance (r = 0.527, p = 0.003), and oxidative stress (r = 0.592, p = 0.016). Leptin correlated with improved insulin resistance (r = 0.449, p = 0.032) while reduced leptin showed a strong association with improved oxidative stress (r = 0.809, p = 0.001). Lastly, reduced oxidative stress correlated strongly with improved insulin-resistance (r = 0.776, p = 0.001).ConclusionsRYGB improves adipose tissue function and inflammation. Leptin as marker for adipose tissue dysfunction may be the mediating factor between insulin resistance and oxidative stress and thereby likely improving T2DM.